2015
DOI: 10.1007/s10637-015-0281-z
|View full text |Cite
|
Sign up to set email alerts
|

Phase I and pharmacological trial of lapatinib in combination with gemcitabine in patients with advanced breast cancer

Abstract: SummaryBackground Lapatinib has proven efficacy as monotherapy and in combination with capecitabine in patients with metastatic breast cancer (MBC) overexpressing HER2 and/or EGFR. Gemcitabine also has anti-tumor activity in MBC and a favourable toxicity profile. In this phase I study lapatinib and gemcitabine were combined. Methods Female patients with advanced BC were given lapatinib once daily (QD) in 28-day cycles with gemcitabine administered on day 1, 8 and 15. Physical examinations, vital signs and bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
(32 reference statements)
2
7
0
Order By: Relevance
“…We observed that transfection with mimic miR-7 suppressed expression of EGFR, IGF-1R and WAVE3 in MDA-MB-231 cells but did not change expression of these proteins in MCF-7 cells. The tyrosine kinase receptors, EGFR and IGF-1R are oncogenes frequently observed to be mutated or amplified in a wide range of solid tumours and have been considered as an important therapeutic target for clinical studies partly because of their involvement in human cancer progression and metastasis ( van der Noll et al , 2015 ). In cancers including breast, lung, colorectal and glioblastoma it has been reported that miR-7 inhibits EGFR and its downstream signalling pathways [31–33].…”
Section: Discussionmentioning
confidence: 99%
“…We observed that transfection with mimic miR-7 suppressed expression of EGFR, IGF-1R and WAVE3 in MDA-MB-231 cells but did not change expression of these proteins in MCF-7 cells. The tyrosine kinase receptors, EGFR and IGF-1R are oncogenes frequently observed to be mutated or amplified in a wide range of solid tumours and have been considered as an important therapeutic target for clinical studies partly because of their involvement in human cancer progression and metastasis ( van der Noll et al , 2015 ). In cancers including breast, lung, colorectal and glioblastoma it has been reported that miR-7 inhibits EGFR and its downstream signalling pathways [31–33].…”
Section: Discussionmentioning
confidence: 99%
“…One possibility was that the comedication had had some influence. However, previous combination studies with lapatinib [22,32], sorafenib [33] and carboplatin [34] showed no clinically relevant influence of concomitant use of these drugs on the plasma PK of gemcitabine.…”
Section: Plasma Pk Of Gemcitabine and Dfdumentioning
confidence: 99%
“…The intracellular PK of gemcitabine, dFdU and their nucleotides was examined in two patient cohorts. Cohort A consisted of 12 female patients who were participating in a phase I study in advanced breast cancer [22], exploring the safety, PK profile and the preliminary antitumour activity of the combination of gemcitabine and lapatinib. Gemcitabine was given as a 30-min intravenous infusion at a dose of 1000 mg m -2 on days 1, 8 and 15 of a 28-day treatment cycle.…”
Section: Study Design and Treatment Schedulementioning
confidence: 99%
“…The target toxicity rate was 33%. The second example is a phase I trial designed to identify the MTD of combination drugs, gemcitabine and lapatinib, for patients with advanced breast cancer 5 . In the trial, gemcitabine was experimented with two doses: 750 and 1000 mg/m 2 , and lapatinib with four doses: 750, 1000, 1250, and 1500 mg. A total of 33 patients were recruited and treated at various dose combinations in cohorts of size three.…”
Section: Introductionmentioning
confidence: 99%